2012
DOI: 10.3233/jad-2012-112102
|View full text |Cite
|
Sign up to set email alerts
|

Amyloid-β25-35 Induces Apolipoprotein D Synthesis and Growth Arrest in HT22 Hippocampal Cells

Abstract: Apolipoprotein D (ApoD) is a secreted glycoprotein that is markedly induced in several pathological and stressful conditions in the nervous system. In the central nervous system, ApoD expression is upregulated during aging, after traumatic brain injury, and in several human neuropathologies such as Alzheimer's disease (AD), where it is found associated with amyloid-β (Aβ) plaques. Recent studies have indicated that ApoD has an important function as a neuroprotective and antioxidant protein. The aim of this wor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 63 publications
2
14
0
3
Order By: Relevance
“…ApoD immunopositive cells within these plaques appear to be reactive microglia, suggesting an inflammation-induced upregulation of ApoD in AD (Desai et al., 2005). Alternatively, Aß itself might induce upregulation of ApoD, as has recently been shown with a hippocampal cell line (Martinez et al., 2012). It remains unclear whether this induction would be direct or indirect, but it is known that Aß triggers production of ROS, which may in turn lead to ApoD upregulation (Butterfield, 2002).…”
Section: Apod In Neurologic Disordersmentioning
confidence: 76%
“…ApoD immunopositive cells within these plaques appear to be reactive microglia, suggesting an inflammation-induced upregulation of ApoD in AD (Desai et al., 2005). Alternatively, Aß itself might induce upregulation of ApoD, as has recently been shown with a hippocampal cell line (Martinez et al., 2012). It remains unclear whether this induction would be direct or indirect, but it is known that Aß triggers production of ROS, which may in turn lead to ApoD upregulation (Butterfield, 2002).…”
Section: Apod In Neurologic Disordersmentioning
confidence: 76%
“…LRRK2 was also detected in the oxidative stress group (Figure 3C) and is upregulated in some cases of sporadic PD (Cho et al., 2013) accompanied by elevated levels of oxidative stress (Nguyen et al., 2011). MPO and APOD , both implicated in AD (Figure 3C) (Maki et al., 2009, Martinez et al., 2012), were strongly downregulated in FTD3 neurons.…”
Section: Resultsmentioning
confidence: 99%
“…The role of Apo D in situations where cellular damage is close related with increased oxidative stress, has been extensively studied by our research group in the last decades Diez-Itza et al, 1994;Lopez-Boado et al, 1994;Martinez et al, 2012Martinez et al, , 2013Navarro et al, 2003Navarro et al, , 2008Navarro et al, , 2010Ordoñez et al, 2006Ordoñez et al, , 2012Perez et al, 2012). In this work, we demonstrated that Apo D is widely overexpressed in both neurons and glial cells of different brain areas in some neurodegenerative diseases such as AD, ME or FTD and also during human aging.…”
Section: Discussionmentioning
confidence: 99%
“…During last decade, different authors have been demonstrated by in vitro assays that molecular agents that cause oxidative stress as hydrogen peroxide (H 2 O 2 ), amyloid beta-peptide or lipopolysaccharide, induce a time and dose-dependent effect on Apo D expression (Do Carmo et al, 2002Lieuallen et al, 2001;Martinez et al, 2012Martinez et al, , 2013Sarjeant et al, 2003). These results could explain, for instance, the high levels of Apo D observed during aging and in several pathological situations like neurodegenerative diseases (Reindl et al, 2001;Thomas et al, 2003b), cancer (Soiland et al, 2007) or obesity (Perdomo et al, 2010).…”
Section: Introductionmentioning
confidence: 99%